2009
DOI: 10.1073/pnas.0908767106
|View full text |Cite
|
Sign up to set email alerts
|

TDP-43 mutant transgenic mice develop features of ALS and frontotemporal lobar degeneration

Abstract: dementia ͉ motor neuron disease ͉ neurodegeneration ͉ protein aggregation F TLD is a relatively common cause of dementia among patients with onset before 65, typically manifesting with behavioral changes or language impairment due to degeneration of subpopulations of cortical neurons in the frontal, temporal and insular regions (1). By contrast, ALS presents with muscle weakness and spasticity due to degeneration of motor neurons in both layer 5 of cortex and in the spinal cord, resulting in death from respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
658
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(701 citation statements)
references
References 32 publications
37
658
5
1
Order By: Relevance
“…In addition, although premature sudden death prevented the assessment of cognitive function in previous studies using mutant TDP-43 transgenic animal models, cortical neuron degeneration has been consistently observed. 11,14,19,20,28 Therefore, our findings in hemizygous TDP-43 M337V mice do not necessarily contradict previous findings only reporting motor dysfunction in TDP-43 transgenic mice. Unlike other transgenic animal models showing increased expression of total TDP-43, the hemizygous TDP-43 M337V model does not demonstrate significantly changed expression of total TDP-43 in the brain and spinal cord, 29 indicating very low transgene expression.…”
Section: Discussionsupporting
(Expert classified)
See 1 more Smart Citation
“…In addition, although premature sudden death prevented the assessment of cognitive function in previous studies using mutant TDP-43 transgenic animal models, cortical neuron degeneration has been consistently observed. 11,14,19,20,28 Therefore, our findings in hemizygous TDP-43 M337V mice do not necessarily contradict previous findings only reporting motor dysfunction in TDP-43 transgenic mice. Unlike other transgenic animal models showing increased expression of total TDP-43, the hemizygous TDP-43 M337V model does not demonstrate significantly changed expression of total TDP-43 in the brain and spinal cord, 29 indicating very low transgene expression.…”
Section: Discussionsupporting
(Expert classified)
“…[11][12][13][14][15][16][17][18][19][20] However, either premature death before the presence of full behavior impairments or extremely aggressive disease progression in many of these animal models make the interpretation of behavioral and neuropathological measurements, especially cognitive assessment, difficult. The TDP-43 M337V transgenic (Tg) mouse (i.e., Prnp-TARDBP* M337V; The Jackson Laboratory, stock no.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of lower MN functional activity is crucial to assess the effect of new treatments, because the loss of neuromuscular function is 1 of the hallmarks of the disease process in ALS animal models [29][30][31]. The results showed that PRE-084 administration significantly improved the amplitude of TA and plantar compound muscle action potential (CMAP), both in female and male SOD1 G93A mice from 12 weeks of age compared to untreated mice.…”
Section: Pre-084 Administration Improves Spinal Motoneuron Function Imentioning
confidence: 99%
“…Deletion of TDP-43 is embryonically lethal, suggesting that dysregulation of RNA metabolism mediated through a TDP-43 defect probably contributes to the toxicity 20 . The TDP-43 mutant transgenic mice developed disease symptoms in the absence of cytoplasmic TDP-43 aggregates, which suggests that the loss-of-function of TDP-43 contributes to its pathogenesis 21 . On the other hand, overexpression of the fulllength or N-terminus-truncated TDP-43 in yeast is toxic and forms cytoplasmic aggregates 22 .…”
mentioning
confidence: 99%